2001
DOI: 10.1017/s0022112001005092
|View full text |Cite
|
Sign up to set email alerts
|

Large-eddy simulation of turbulent gas–particle flow in a vertical channel: effect of considering inter-particle collisions

Abstract: The interaction between a turbulent gas flow and particle motion was investigated by numerical simulations of gas–particle turbulent downward flow in a vertical channel. In particular the effect of inter-particle collision on the two-phase flow field was investigated. The gas flow field was obtained by large-eddy simulation (LES). Particles were treated by a Lagrangian method, with inter-particle collisions calculated by a deterministic method. The spatial resolution for LES of gas–solid two-phase turbule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
204
2
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 324 publications
(224 citation statements)
references
References 29 publications
12
204
2
1
Order By: Relevance
“…The first LES of particle-laden flow, in particular, was performed under the assumption of negligible contribution of the SGS fluctuations to the filtered fluid velocity seen by inertial particles [11]: The choice was justified considering that inertial particles act as low-pass filters that respond selectively to removal of SGS flow scales according to a characteristic frequency proportional to 1/τ p , where τ p is the particle relaxation time (a measure of particle inertia). The same assumption has been used in other studies [12][13][14][15] in which the filtering due to particle inertia and the moderate Reynolds number of the flow had a relatively weak effect on the (one-particle, two-particles) dispersion statistics examined. However, several studies [16][17][18] have demonstrated that neglecting the effect of SGS velocity fluctuations on particle motion leads to significant errors in the quantification of large-scale clustering and preferential concentration, two macroscopic phenomena that result from particle preferential distribution at the periphery of strong vortical regions into low-strain regions [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…The first LES of particle-laden flow, in particular, was performed under the assumption of negligible contribution of the SGS fluctuations to the filtered fluid velocity seen by inertial particles [11]: The choice was justified considering that inertial particles act as low-pass filters that respond selectively to removal of SGS flow scales according to a characteristic frequency proportional to 1/τ p , where τ p is the particle relaxation time (a measure of particle inertia). The same assumption has been used in other studies [12][13][14][15] in which the filtering due to particle inertia and the moderate Reynolds number of the flow had a relatively weak effect on the (one-particle, two-particles) dispersion statistics examined. However, several studies [16][17][18] have demonstrated that neglecting the effect of SGS velocity fluctuations on particle motion leads to significant errors in the quantification of large-scale clustering and preferential concentration, two macroscopic phenomena that result from particle preferential distribution at the periphery of strong vortical regions into low-strain regions [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Consistent LES then means tracking a reduced number of drops; 'computational' drops are thus used to represent the physical drops. In this context, TP LES has additional modelling requirements compared to SP LES; whereas DNS requires modelling the interaction between individual drops and the unfiltered flow field, in LES neither the individual drops nor the unfiltered flow field are available and their interaction must be modelled from that between the filtered flow field and the computational drops.Recent LES of TP flows include those by Deutsch & Simonin (1991), Simonin, Deutsch & Boivin (1993, Uijttewaal & Oliemans (1996), Wang & Squires (1996), Boivin, Simonin & Squires (2000, and Yamamoto et al (2001). These LES all considered an incompressible gas phase laden with small solid particles, with the particles not affecting the evolution of the gas phase, i.e.…”
mentioning
confidence: 99%
“…Wang & Squires (1996) found SGS effects, included by modifying the gas-phase velocity felt by the particles, to be negligible. The LES of Boivin et al (2000) and Yamamoto et al (2001) included two-way coupling, but still neglected SGS effects on the particles. The SGS modelling requirement in these studies was confined to the gas phase, facilitating the use of the large body of work on SGS flux models for incompressible SP flow.…”
mentioning
confidence: 99%
“…Results from LES and direct numerical simulation (DNS) of particle-laden turbulent flows have shown that singleparticle statistics, such as the turbulent dispersion of particles, is not significantly affected by the subgrid-scale (SGS) motions of LES, except near the wall, as they are mainly controlled by large-scale eddies, but particle-pair statistics, such as particle collision and preferential concentration, are sensitive to small-scale eddies (Yeh and Lei 1991;Uijttewaal and Oliemans 1996;Wang and Squires 1996;Armenio et al 1999;Yamamoto et al 2001;Fede and Simonin 2006). Therefore, in the present LCM, the transport of a droplet is calculated by following the trajectory of a Lagrangian droplet using LES, while the collision/coalescence process and preferential concentration are parameterized.…”
Section: Model Descriptionmentioning
confidence: 99%